Androgen actions regulating TRIB1/3 in prostate cancer: effects on cell proliferation, survival, and metabolism - Shologu, Ziyanda (2023)
Prostate cancer (PCa) is an androgen-sensitive neoplasia with cell survival and proliferation being dependent on androgenic regulation. At this stage, PCa cases can be treated with androgen deprivation therapy (ADT), which aims to decrease the circulating levels of androgens or block their actions. However, genetic alterations including the fusion of genes, amplification of oncogenes, gene mutations and deletions concur promoting the advance of the disease to more aggressive forms. Following this, phenotypic/behaviour changes such as loss of androgen sensitivity occur, allowing the cancer cells grow even if circulating androgens are low. It is the so-called castrate resistant prostate cancer (CRPC). A well-established observation ‘in several cancer cell types is the Warburg effect’, the metabolic reprogramming that enables cancer cells to survive, proliferate and metastasize, using high amounts of glucose as energy substrate, both in aerobic and anaerobic conditions. Tumour cells using glycolysis to maintain energy needs, subsequently produce high amounts of lactate that is exported to the extracellular medium. In the case of PCa, the metabolic reprogramming towards the more glycolytic phenotype accompanies the progression of disease to the CRPC. It was demonstrated that androgens are important regulators of PCa cells metabolism, enhancing glycolysis as well as lipid handling. The pseudokinase family Tribbles (TRIBs), which includes TRIB1, TRIB2 and TRIB3, has been described to have a role in controlling differentiation, transcription, proliferation, and metabolism. These pseudokinase proteins are characterized by functioning as scaffold-like or adaptor molecules in many signalling pathway networks including mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K-AKTf) modules. Consistent with the described actions and the control of intracellular signalling, TRIBs have being involved in disease development, as well as are implicated in several cancers. Evidence indicates the oncogenic role of TRIB1 and TRIB3 and their highly expressed state in tumour initiation and progression, especially in melanoma, lung, liver, and acute leukemia, but also in PCa. Yet, the mechanisms that control TRIBs expression in PCa are still poorly understood. Moreover, the involvement of TRIB1 and TRIB3 in lipids homeostasis has been demonstrated. The main goal of this thesis was to investigate the role of androgens in regulating TRIB1 and TRIB3 expression in PCa and to shed light on the influence of TRIBs on prostate cell fate. The androgenic modulation of TRIBs in PCa cells was determined using 10 nM 5α-dihydrotestosterone (DHT), in the presence or absence of the anti- androgen bicalutamide (10 μM). DHT treatment decreased TRIB1 and TRIB3 expression at a protein and mRNA level in the androgen sensitive LNCaP and 22Rv1 cells with no changes observed in the non-neoplastic PNT1A cells. Bicalutamide (10 μM) blocked the effect of DHT in down-regulating TRIB1 expression in LNCaP and 22Rv1 cells, which suggests the involvement of the androgen receptor (AR). These findings were validated by the expression analysis of the standard androgen- responsive gene prostate-specific antigen (PSA), confirming its increased expression in DHT treated cells and blocking of effects by bicalutamide. To further study the impact of the AR in TRIB1 regulation, we performed a knockdown (KD) of the AR in LNCaP and 22Rv1 cells and measured TRIB1 expression. AR KD resulted in a significant TRIB1 increase in 22Rv1 cells at an mRNA level. These outcomes are in line with those obtained in-vivo, as castrated mice displayed increased TRIB1 mRNA expression levels compared to control, which highlights the androgens’ regulatory effects of TRIBs in PCa. Moreover, using ChiP-seq analysis in human primary tumours vs normal solid tissues it was shown that AR directly binds to the TRIB1 and TRIB3 gene locus. LNCaP cells treated with the synthetic androgen r1881 also showed a similar pattern of TRIBs downregulation. Together these findings provide useful insight into AR actions in regulating TRIB1 expression in PCa. Concerning the physiological effects on PCa cell fate, enhanced cell viability, proliferation and migration were observed in androgen treated cells, whereas no alterations were seen on caspase-3 activity. TRIBs associated signalling pathways targets such as pERK and pAKT, prominently known to have roles in survival, apoptosis, and differentiation in response to a range of stimuli including steroid hormones were also measured after 10 nM DHT treatment and downregulation of their expression was observed. TRIB1 has been shown to be overexpressed in PCa and associated with the progression of disease. However, it is not clear if is the TRIB1 increased expression levels that promote the malignant transformation of prostate cells. Therefore, the influence of TRIB1 expression levels in non-neoplastic (PNT1A) and neoplastic (PC3) prostate cells fate was investigated. TRIB1 overexpression (OE) on PNT1As increased cell proliferation and migration, with no changes on caspase-3 activity and cell viability. The effect of TRIB1 OE on lipid metabolism was also measured and a significant increase of lipid droplets was observed in PNT1A cell OE TRIB1. This was accompanied by the increased expression of fatty acid synthase (FASN), a key target protein in lipid metabolism in neoplastic conditions. Overall, TRIB1 OE changed the features of non-neoplastic PNT1A cells to a cancer-like phenotype. Interestingly, no changes were observed on the viability, proliferation and metabolism of TRÎB1 knockdown PC3 cells. These results implicate TRIB1 in the regulation of metabolism, as well as suggest its role as a ‘driving force’ for tumour initiation and progression of disease in the early stages of PCa development. In summary, this dissertation demonstrated the androgen actions in the regulation of TRIBs in PCa cells. Revealing the link between TRIBs, androgens and AR in PCa development and progression. Collectively, further research on these interaction warrants TRIBs as a basis for the development of new therapeutic approaches for PCa.